Young Talents in Polymer Science - Alexander Böker (Ed.); Frank Wiesbrock (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Polymers aims to compile the current trends and research directions of internationally renowned and successful young polymer scientists in one dedicated Special Issue. The idea for this Special Issue has arisen from the numerous and, above all, brilliant nominations for our 1st Young Investigator Award. It was the easiest-ever choice for us to publicly share the fascinating and thrilling research successes of the nominated scientists with you, our dear peer readers. For this prestigious Special Issue, the journal Polymers will only accept original research papers that have been invited exclusively by the editors. The contributions to this Special Issue will highlight the current state-of-the-art in the fields of polymerization methods, theory/simulation/modeling, new physical phenomena, advances in characterization techniques, and harnessing of self-assembly and biological strategies for producing complex multifunctional structures. Please enjoy reading these high-end research highlights!